The Folktale Narrator at the Turn of the 20th – 21st Century: the Case of Antanina Čaplikienė from Subartonys - Šlekonytė, Jūratė (Tautosakos darbai, 2022)
In the course of the fieldwork in 2000, researchers from the Institute of Lithuanian Literature and Folklore encountered a villager from Subartonys (Varėna district) Antanina Glaniauskaitė-Čaplikienė (1922–2016). In the course of five subsequent years, they recorded from her 140 folk narratives altogether (including 69 folktales, 9 folk-belief legends, 3 place legends, 6 dream narratives, 40 biographical narratives, and several anecdotes). The major part of the Čaplikienė’s repertoire consisted of folktales that were rather well known in the Lithuanian culture, including a number of narratives typical for the Dzūkija region. The author is curious about the ways that Čaplikienė managed to preserve such a vivid folkloric memory. In order to elucidate this, she uses the branch of the contextual research on storytelling developed by the Hungarian folklorist Linda Dégh – namely, the folktale biology (Märchenbiology). The study focuses on these aspects: 1) in view of the Dzūkija folklore tradition in general and the Čaplikienė’s life in particular that shaped her as a storyteller, the woman’s narrative repertoire is discussed, including the number and genre affiliation of her stories, and their place in the Lithuanian folk narrative tradition; 2) Čaplikienė’s memories regarding the folktale narration in the past are analyzed, including the sources that she had learnt her pieces from, and her mode of communication with the folklorists that recorded her tales. The aim of the article is to highlight the uniqueness of this storyteller at the turn of the 20th – 21st centuries and in the context of the folk narrative tradition of Dzūkija.
Keywords: folktales; storyteller; Dzūkija; folkloric memory; tall-tale tellers